Tear exosome‐based PROteolysis TArgeting Chimeras nanomedicine for human immunodeficiency virus‐mediated cancer treatment - Nobendu Mukerjee (Wiley, 2024)
Abstract Human Immunodeficiency Virus (HIV) significantly increases the risk of various cancers due to chronic immune suppression and viral oncogenes. Traditional therapies, including antiretroviral therapy (ART), chemotherapy, and radiation, often face limitations such as drug resistance and systemic toxicity. PROteolysis TArgeting Chimeras (PROTACs) have emerged as a promising approach for targeted protein degradation, offering significant advantages over conventional treatments. However, effective delivery remains a challenge. This paper explores the innovative use of tear exosome‐based delivery systems for PROTACs in treating HIV‐mediated cancers. Tear exosomes, due to their natural origin, biocompatibility, and inherent targeting capabilities, present a novel and effective platform for delivering PROTACs, enhancing therapeutic specificity and reducing adverse effects. Integrating the unique properties of tear exosomes with the therapeutic potential of PROTACs could revolutionize the treatment of HIV‐mediated cancers by overcoming current therapeutic challenges and improving patient outcomes.